Organization of service of internal audit and method of his conducting - Shulga, A. V.; Toporkova, O. A. (Science and Transport Progress, 2012)
Actuality of leadthrough of internal audit of financially-economic activity of business entity is certain. Basic functions, principles of construction, methodical receptions, are considered, the criteria of estimation of efficiency of internal audit are certain.